Tinjauan Hukum terhadap Force Majeure Sebagai Dasar Pembenaran Kredit Macet - Anak Agung Dewi Utari (Wajah Hukum, 2026)
Bad debt is a common problem in banking practices and has direct implications for the stability of financial institutions and legal certainty in the relationship between banks and debtors. In various credit agreement disputes, debtors often submit force majeure as a reason for the inability to fulfill payment obligations. Legal issues arise when the concept of force majeure in civil law cannot automatically be applied to every condition of economic difficulty or change in circumstances experienced by the debtor. This is the reason why the author chose the title Analysis of Force Majeure as the reason for Bad Debt. Because often the general public does not understand the true meaning of force majeure, and makes force majeure as an act of neglecting obligations. This study aims to analyze the legal position of force majeure in banking credit agreements and examine the limits of its application as a reason for exemption from responsibility for bad debt. This research is a normative legal research with a statutory and conceptual approach, supported by a literature study using primary and tertiary legal materials. The research results show that force majeure can only be used as a basis for exemption from liability if it meets the elements of unforeseen circumstances, is beyond the debtor's control, is unavoidable, and has a direct causal relationship to the failure to fulfill the obligation. Therefore, not every bad debt can be justified based on the force majeure argument